Spleen assessment after laparoscopic transperitoneal left adrenalectomy: preliminary results - Cianci, Pasquale (Surg Endosc, 2015)
BACKGROUND: Several laparoscopic approaches to the adrenal gland have been described. We prefer the lateral transabdominal approach. The aim of this study is to evaluate prospectively the presence of any anatomical and dynamic changes in the spleen after laparoscopic transperitoneal left adrenalectomy (LTLA), which can cause an increased risk of early and late complications. METHODS: We have evaluated 21 patients before and 6 months after surgery in order to verify the possible presence of a wandering spleen. A clinical and instrumental follow-up [ultrasound (US), magnetic resonance (MR)] were performed. During US protocol, in supine, right lateral, and orthostatic position, the longitudinal and anteroposterior diameter of the spleen and the resistive index within 3 cm of the origin of the splenic artery in three different measurements averaged were measured. MR protocol evaluated, in supine and right lateral position, the splenic volume and its distances from the diaphragm dome and the lateral margin of the costal arch. RESULTS: p Values calculated for each parameter were not statistically significant. Our results confirm the absence of any anatomical and dynamic changes in the spleen after LTLA. CONCLUSIONS: The most common complications after laparoscopic adrenalectomy are well known and widely described. Our experience does not exclude the occurrence of a wandering spleen, but allows us to state that a rightful mobilization of the pancreaticosplenic block can avoid this event, and in agreement with other authors, the presence of a wandering spleen remains an isolated complication.